Motivasi Siswa terhadap Pembelajaran Seni Budaya (Seni Musik) pada Kelas VIII C di SMPN 2 Batang Gasan - Anggra Pratiwi; Yensharti Yensharti (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
Cultural arts learning is one of the compulsory subjects taught at the Junior High School (SMP) level. Through cultural arts at school, students are able to express themselves and channel their creativity. In learning, student motivation is an important factor in determining student success in achieving understanding. Because motivation will influence a person's desire to do something. This study was conducted to describe student motivation towards learning cultural arts (music) in class VIII C at SMPN 2 Batang Gasan District. In conducting this study, the researchers employed a quantitative approach with a descriptive method. The study focused on grade VIII students of SMPN 1 Batang Gasang, with the sample group being determined using the cluster random sampling technique. The selected sample consisted of students from class VIII C. To gather data, a questionnaire was distributed to the students, which was designed based on indicators of intrinsic and extrinsic learning motivation. The collected data was then analyzed using the average equation and subjected to descriptive analysis. Based on the results of the research obtained, it can be concluded that student motivation towards learning cultural arts (music) in class VIII C at SMPN 2 Batang Gasan District is obtained for internal motivation with an average value of 75.7% in the high category. As for extrinsic motivation, the average value is 65.32% in the high category. Overall, student motivation obtained an average value of 70.51% in the high category. Therefore, student motivation at SMPN 1 Batang Gasan can be categorised as high towards learning cultural arts, especially in music.